Paraben residues in wastewater and surface water: a case study of KwaZulu Natal and Gauteng provinces (South Africa) during the COVID-19 pandemic - Mpayipheli, Neliswa; Mpupa, Anele; Madala, Ntakadzeni Edwin; Nomngongo, Philiswa Nosizo (Frontiers in Environmental Science, 2024)
The occurrence of parabens (methylparaben (MePB), ethylparaben (EtPB), propylparaben (PrPB), and butylparaben (BuPB) was investigated in wastewater samples from various wastewater treatment plants (WWTPs) and the receiving surface waters in KwaZulu Natal and Gauteng Provinces (South Africa). The samples were collected between October 2020 and December 2021, covering the 2 nd , 3 rd and 4 th waves of the COVID-19 pandemic. A solid phase extraction protocol with high-performance liquid chromatography was used to extract and enrich parabens before analysis. Methylparaben (2.02-84.7 µg/L),